Ta’dib-Based Islamic Education Shapes Morals in The Era of Industrial Revolution 4.0 - Rochman, Fauzi; Albany, Sulistiono Shalladdin; Mursyid, Muhammad (Universitas Ahmad Dahlan, 2023)
The purpose of this writing is to explain ta’dib-based Islamic education that shapes morals in the era of the Industrial Revolution 4.0. This is done to formulate educational concepts so that they can be used to shape morals. This research method is library research by collecting data from documentation using the descriptive-analysis method. Based on the presentation and results of the discussion, it can be concluded that the appropriate concept of Islamic education is the concept of ta’dib. Because in the concept of ta’dib there are the concepts of ta’lim and tarbiyah. The concept of ta’dib unites faith, knowledge, and charity to form morals. The concept of the ideal human according to the concept of ta’dib is: 1) Producing manners towards oneself. 2) Adab in relationships between human beings. 3) Etiquette in the context of science. 4) Adab in the context of relationships with nature. 5) Adab towards language. 6) adab in the context of the spiritual realm.